A Study of Work-Life Balance among Managers of Public and Private Sector Banks - Prabhu, Vinay V.; Pithadia, Bharat M. (SFIMAR Research Review, 2016)
Work life and personal life are inter-connected and interdependent. Spending more time at work can interfere and affect personal life. On the other hand, personal life can also be very demanding and severely disrupt work life. The need to strike a good work-life balance has become imperative. Worklife balance is about creating and maintaining a supportive and healthy work environment, which will enable employees to have a balance between their work and personal responsibilities. A number of studies have found that a good work-life balance has become the mantra of young India. In fact young India gives more importance to work-life balance than job security. Organizations in India have also woken up to the changing needs of their workforce and are using a good work-life balance as key HR strategy for attracting and retaining talented employees. This research paper investigated work-life balance in managers of private and public sector banks. The study found that the overall levels of work-life balance was low among bank managers. There was no significant difference in the work-life balance of managers of private sector banks and public sector banks. However, there were significant differences in the various factors contributing to work-life balance among managers in private and public sector banks.